If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = 1 + -2y Solving -7 = 1 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -7 + 2y = 1 + -2y + 2y Combine like terms: -2y + 2y = 0 -7 + 2y = 1 + 0 -7 + 2y = 1 Add '7' to each side of the equation. -7 + 7 + 2y = 1 + 7 Combine like terms: -7 + 7 = 0 0 + 2y = 1 + 7 2y = 1 + 7 Combine like terms: 1 + 7 = 8 2y = 8 Divide each side by '2'. y = 4 Simplifying y = 4
| X^2-39=10 | | 4x^3/3y | | 8×2/3= | | 2(x+5)+2x=50 | | 6=10+2x | | 4=3x+39 | | 2m+6m=102 | | 13t+10=-65 | | X+4(X+6)=1 | | 8-w=-23 | | 0.25p+0-2(10-p)=0 | | 2(x+1)-x-1=1 | | x(5+2x)=532 | | 13t+10=-65whatisT | | 8z-18=2z | | 3x-2(00)=-6 | | 8x+15x-6=40 | | 9x^3+3x^2+3x+1=0 | | 7.75=a-259 | | 4x+7=5x+17-2x | | https://lh5.googleusercontent.com/3z6e-yOwAdr5KjfGYBzzsqpEiae12YjG86rjzwQDvfEsP-fkI94mrrTNu3FV2Kc6pVLGzne5OA=w126 | | 20=4(x+7)-2 | | x=24-3(2x+1) | | 3f-9=14f+1 | | 8y-20=4y | | (x)(2+3x)=320 | | h(n-4)=-3n-4 | | 13m+4w=1223 | | x/12-18=31 | | 60+20m=720 | | 2x^2+2y^2-4x+4y+18=O | | 6(-7p-8)=-90 |